Kethoprak Reog Paguyuban Seni Reog Singo Bhirowo Lakon Suminten Edan (Kolaborasi Kesenian Rakyat sebagai Ekspresi Akulturasi Budaya) - Dipoyono, Achmad; Imama, Yulela Nur (Acintya, 2023)
ABSTRACT The city of Surakarta has approximately 35 groups or communities dedicated to the Reog art form. One of these groups is known as "Paguyuban Seni Reog Singo Bhirowo" which comprises 45 members spanning across different generations. This quantity reflects the high level of interest among the Banjarsari community in Reog art. Moreover, the establishment of "Paguyuban Seni Reog Singo Bhirowo" is a response from urban residents living outside Surakarta who have a background in Reog art. The group aims to create a performance format that combines Reog with the traditional Javanese art form called "Kethoprak," known as "Reog Kethoprak." The fusion of Kethoprak and Reog, both rooted in folk art, is seen as a suitable step to promote intercultural understanding, tolerance, and enrich the global heritage of the arts. This cultural amalgamation in the presentation of Kethoprak and Reog is an offering to strengthen their coexistence in society, particularly in Surakarta. The process of creating the Reog Kethoprak performance, exemplified by the Suminten Edan play, involves various stages: cultural exchange, acceptance and exploration, adoption and adaptation, integration, and transformation, resulting in the final show. In the implementation of the Suminten Edan play, contemporary conflicts related to the economic situation of the Reog community are incorporated into the narrative. The collaboration between these two folk art forms, Kethoprak and Reog, serves as a reflection of cultural tolerance and a recognition that differences can come together to produce something significant and have a positive impact on each other. This collaboration is not about division or competition but rather about unity. Keywords: Acculturation, Reog Kethoprak, Local Cultural Expression.